DOP24 Early life exposures and risk for inflammatory bowel disease: a nested case-control study in Quebec, Canada. (30th January 2023) - Fantodji, C; Rousseau, M C; Nicolau, B; Madathil, S; Benedetti, A; Jantchou, P
Abstract: Background: Early childhood is an important period for the establishment of gut microbiota. Most early life risks or protective factors for inflammatory bowel disease are likely to act through an effect on the gut microbiota. The aim of this study was to estimate the associations between exposures in infancy (birth until 3 years of age) such as breastfeeding, antibiotic treatment, presence of domestic pets, and passive smoking, and the occurrence of inflammatory bowel diseases. Methods: This case-control study was nested within the Quebec Birth Cohort on Immunity and Health. Cases and controls were identified among persons born in Quebec in 1970-1974 based on their health services from 1983 to 2014 using validated algorithms. All cases and randomly selected controls were invited to participate in a web or telephone questionnaire. Participation rates were 47% among controls (n=946), and respectively 52% (n=1212) and 55% (n=570) among cases of Crohn's disease and ulcerative colitis. Logistic regression models were used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI), separately for Crohn's disease and ulcerative colitis. Each exposure was analyzed in a multiple regression model adjusted for relevant covariates identified with a directed acyclic graph. Results: Adjusting for perinatal and sociodemographic characteristics, the risk for Crohn's disease or ulcerative colitis did not differ in subjects who were exclusively breastfed compared to non-breastfed subjects. Partial breastfeeding (breastfeeding combined with infant formula) was not associated with Crohn's disease (OR=1.03, 95% CI: 0.76-1.40), but an increase in the odds of ulcerative colitis (OR=1.40, 95% CI: 0.99-1.99) was observed as compared with no breastfeeding. Early introduction of solid foods was associated with higher odds of Crohn's disease (introduction at 3-6 months compared with >6 months: OR=1.35; 95% CI: 1.05-1.78), but not of ulcerative colitis (OR=1.06; 95% CI: 0.77-1.46). Antibiotic use and the presence of domestic pets were not associated with either Crohn's disease or ulcerative colitis. Passive smoking was associated with increased odds of Crohn's disease (OR=1.23; 95% CI: 1.00-1.51), but not ulcerative colitis (OR=0.96; 95% CI: 0.75-1.22). Conclusion: Differences were noticed in early childhood risk factors for Crohn's disease and ulcerative colitis. Early introduction of solid foods and passive smoking increased the risk of Crohn's disease, whereas there was a trend of increased risk of ulcerative colitis with partial as compared with no breastfeeding. The results for partial breastfeeding and early introduction of solid foods are novel and will require further investigation.